Enhancing the Decolorizing and Degradation Ability of Bacterial Consortium Isolated from Textile Effluent Affected Area and Its Application on Seed Germination. (11th January 2015) - Mahmood, Rashid; Sharif, Faiza; Ali, Sikander; Hayyat, Muhammad Umar
Abstract : A bacterial consortium BMP1/SDSC/01 consisting of six isolates was isolated from textile effected soil, sludge, and textile effluent from Hudiara drain near Nishat Mills Limited, Ferozepur Road, Lahore, Pakistan. It was selected because of being capable of degrading and detoxifying red, green, black, and yellow textile dyes. The pH and supplements were optimized to enhance the decolorization ability of the selected consortium. The results indicated that decolorizing ability of consortium for the red, green, black, and yellow dyes was higher as compared to individual strains. The consortium was able to decolorize 84%, 84%, 85%, 85%, and 82% of 200 ppm of red, green, black, yellow, and mixed dyes within 24 h while individual strain required 72 h. On supplementing urea, the consortium decolorized 87, 86, 89, 86, and 83%, respectively, while on supplementing sodium chloride the consortium decolorized 93, 94, 93, 94, and 89% of red, green, black, yellow, and mixed dyes, respectively, which was maximum while in the presence of ascorbic acid and ammonium chloride it showed intermediate results. The effect of untreated and treated dyes was investigated on Zea mays L. (maize) and Sorghum vulgare Pers. (sorghum). This study will help to promote an efficient biotreatment of textile effluents.